Black Male School Leaders: Protectors and Defenders of Children, Community, Culture, and Village. Issue 1 (January 2021) - Smith, Phillip A.
This study explored the ways in which the race-gendered identities and lived experiences of Black male K-12 public and independent school leaders inform their leadership in support of students, community, and village. The study draws from critical theories and perspectives, including a framework of Black Masculine Caring (BMC), critical race theory, culturally relevant and responsive leadership, leadership for social justice, and their relationship to and with a theory of Black male school leadership. The qualitative study used survey, phenomenological, and visual elicitation methods to examine the personal and professional experiences, philosophies, and praxis of 14 Black male school leaders. Study findings are presented as an intergenerational dialog with participants, based on their years of leadership experience. These leaders exhibit a liberatory care-based approach to leadership as an expression of social justice advocacy, civil rights activism, community and evidenced action-orientated commitment to a dismantling of structured and systemic forms of racism, anti-Black racism entrenched segregation, and other inequities that discriminate and disproportionately marginalize significant numbers of students and their communities. As captured through the narratives shared, this is evidenced through greater, and positively encouraged, levels of parental and other community member involvement in school activities, as a core aspect of the leadership and decision-making processes. The research expands understanding of paradigms of critical race leadership and disrupts the normative educational leadership that ill-serve significant sections of our student populations and communities.